Mechanical and durability properties of steel fiber-reinforced concrete containing coarse recycled concrete aggregate - Kaplan, Gokhan; Bayraktar, Oguzhan Yavuz; Gholampour, Aliakbar; Gençel, Osman; Koksal, Fuat; Ozbakkaloglu, Togay; Gençel, Osman (Ernst & Sohn, 2021)
The focus of this study is to investigate the effect of using coarse recycled concrete aggregates (RCAs) as an alternative material to natural coarse aggregate on the fresh, mechanical and durability behavior of concrete reinforced with steel fiber. Eighteen unique concrete mixes with RCA content of 0%, 50%, and 100% and steel fiber content of 0%, 1%, and 2% were prepared, and tests were performed to study slump, density, compressive and splitting tensile strengths, flexural behavior, surface hardness, surface abrasion resistance, water absorption, and sorptivity of each mix. It is shown that concrete containing RCA has a lower unit weight, compressive, splitting tensile and flexural strength, flexural toughness, surface hardness, and abrasion resistance, and a higher water absorption and sorptivity in comparison with conventional concrete. An increased compressive, splitting tensile and flexural strength, flexural toughness, surface hardness, and abrasion resistance, and a decreased water absorption and sorptivity of concrete with an increased steel fiber content from 1% to 2% is less significant compared to those from 0% to 1%. The results also show that, at RCA content of 50%, incorporating 1% steel fiber develops a concrete mix with similar or even better properties compared to unreinforced conventional concrete. At 100% RCA content, incorporating 2% steel fiber develops a concrete mix with similar properties to unreinforced conventional concrete having water to cement ratio of 0.3, but inferior properties to unreinforced conventional concrete having water to cement ratio of 0.5. These findings indicate that recycled aggregate concrete with similar or even better properties compared to concrete with natural aggregate can be developed through properly designing mixes, providing a great avenue toward the production of green construction material for structural applications.
Keywords: Coarse Recycled Concrete Aggregate (Rca); Durability; Flexural Toughness; Steel Fiber; Strength